Development of a scale for use in monitoring training-induced distress in athletes - Raglin, J. S.; Morgan, W. P. (International Journal of Sports Medicine, 1994)
Items from the Profile of Mood States were used to predict the state of distress associated with swimming training. Coaches' opinions of their swimmers' states were used to signal the existence of intensive training stress. Over four competitive seasons data were collected on 70 female and 100 male swimmers. Responses to the POMS were regressed to predict whether or not Ss were distressed. When all information was included the accuracy for predicting males was 93.9% and females 100%. Seven POMS items were consistently indicated as being predictors. When those seven items were used to predict a sample of 33 male swimmers on a monthly basis accuracy ranged from 55.6% to 79.8% with an average of 69.1%. This level of accuracy was cross-validated with track and field athletes. The seven POMS items most commonly appearing in the analyses were: worthless, miserable, guilty, unworthy, sad (all from the depression scale), and bad-tempered and peeved from the anger scale. Implication: The content of the POMS for predicting overtrained or overreached states involve the depression and anger scales. The items indicate negative, depressed, and intolerant features. Without actually giving a test, a coach can determine that if athletes are negative, bad-tempered, depressed, and lacking in confidence then accentuated rest (restoration) is in order.